School Teachers: Job Stress and Job Satisfaction, Kaski, Nepal - Jaita Mondal; Sandhya Shrestha; Archana Bhaila (Occupational Health and Safety Society of Nepal, 2011)
In teaching profession, distress has been linked to dissatisfaction with job and to negative affective and profes sional consequences. In the present study, the attempt was made to identify the level of job stress and job satisfaction among teachers in consideration with their gender differences along with age and experiences. Study comprised of randomly selected 69 school teachers from Pokhara, Nepal. Socio economic data of the subjects were collected by questionnaire. Modified TJSQ and Modified TARSO were applied to identify the Job satisfac tion and Job stress of the subjects. Data from acceptable returned questionnaires were analyzed by SPSS 17. It can be concluded from the analysis that, the school teachers were partly satisfied and experiencing mild to moderate stress from their job overall. These can be the resultant of unfavorable job condition and job types for the school teachers.